2021
DOI: 10.1186/s40101-021-00265-x
|View full text |Cite
|
Sign up to set email alerts
|

The establishment of serum 25-hydroxyvitamin D reference intervals in children aged 0–14 years in Zigong area, China

Abstract: Objective To establish the reference interval of serum 25-hydroxyvitamin D (25(OH)D) in apparently healthy children in Zigong, China, using an indirect method to provide a basis for proper clinical diagnosis and treatment. Methods A total of 1851 apparently healthy children of the Children’s Health Care Department in Zigong First People’s Hospital between January 2016 and December 2020 were included in the study. The Kolmogorov–Smirnov test was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…Our findings indicated that there were statistically significant variations in the 0 ~ ≤ 1 year, 2 ~ ≤ 3 years, 4 ~ ≤ 6 years, and 7 ~ ≤ 18 years age groups (all P < 0.001), and the serum 25(OH)D levels decreased with age increasing, which is in agreement with prior studies [ 17 19 ]. The trend may be attributed to the young children's daily intake of vitamin D-rich infant formula as well as fortified baby foods, while adolescents' lack of outdoor activities and inadequate vitamin D supplementation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings indicated that there were statistically significant variations in the 0 ~ ≤ 1 year, 2 ~ ≤ 3 years, 4 ~ ≤ 6 years, and 7 ~ ≤ 18 years age groups (all P < 0.001), and the serum 25(OH)D levels decreased with age increasing, which is in agreement with prior studies [ 17 19 ]. The trend may be attributed to the young children's daily intake of vitamin D-rich infant formula as well as fortified baby foods, while adolescents' lack of outdoor activities and inadequate vitamin D supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…It was discovered that the serum 25(OH)D levels during summer were significantly lower compared to autumn, while higher than in winter (all P < 0.001). The findings for the seasonal fluctuation in serum 25(OH) levels were close to those from other research projects carried out in the Zigong area and southern China [ 17 , 20 ]. The varying levels of 25(OH)D can be explained by the amount of sunlight exposure, since it is mainly acquired through exposure to the sun's UV rays that activate its production in the skin.…”
Section: Discussionsupporting
confidence: 87%